Socioeconomic and ethnic segregation in Finland: A multi-scale analysis of diverse urban sizes - Kurvinen, Antti; Karhula, Aleksi; Ala-Mantila, Sanna (ELSEVIER SCI LTD, 2025)
Rising residential socioeconomic segregation is a globally acknowledged phenomenon that also occurs in the Nordic welfare states. Our study provides a comprehensive view of residential socioeconomic and ethnic segregation across 20 Finnish cities, including both large and smaller cities. We highlight the importance of the scale of analysis by comparing the results from a residential area classification to other neighbourhood definitions, including zip code and statistical grid levels. Instead of relying on a single city-level indicator, we also zoom into different residential area types and illustrate the development of their socioeconomic and ethnic structure between 2000 and 2018. The results show increasing levels of socioeconomic segregation in all studied cities and scales. The increasing levels of segregation are linked to the relative deprivation of residential mid-rise areas built from the 1960s until the 1990s and to the increasing positive selection by income and education in the residential low-rise areas built after 2000. The results for ethnic segregation are more diverse showing increases in some cities but decreases in others. The overall average of ethnic segregation in the 20 studied cities has slightly decreased although ethnic minorities are still overrepresented in the socioeconomically disadvantaged residential areas.